Liability-of-foreignness effects on job success of immigrant job seekers - Tony Fang; Al-Karim Samnani; Milorad M. Novicevic; Mark N. Bing (Institute for the Study of Labor (IZA), 2012)
We examined the liability-of-foreignness (LOF) hypothesis for immigrant and native job seekers by analyzing a national dataset that tracks their use of job-search methods and their associated job outcomes in the Canadian labor market. To our knowledge this is the first empirical test of LOF at the individual-level while controlling for variables at multiple levels. We found support for LOF when job applicants used the rich media job-search methods of social networks and recruitment agencies, but not when they used the lean media of newspaper ads and the internet. Study limitations, implications, and future research are discussed.
Keywords: J15; J71; J78; 330; liability-of-foreignness; immigration policy; levels of analysis; job success; labor market; Migranten; Bevölkerung; Arbeitsuche; Erwerbsverlauf; Schätzung; Kanada